Directly imaging damped Ly α galaxies at z > 2 – III. The star formation rates of neutral gas reservoirs at z ∼ 2.7. Issue 3 (5th December 2014) - Fumagalli, Michele; O'Meara, John M.; Prochaska, J. Xavier; Rafelski, Marc; Kanekar, Nissim
Abstract: We present results from a survey designed to probe the star formation properties of 32 damped Lyman α systems (DLAs) at z ∼ 2.7. By using the 'double-DLA' technique that eliminates the glare of the bright background quasars, we directly measure the rest-frame far-ultraviolet flux from DLAs and their neighbouring galaxies. At the position of the absorbing gas, we place stringent constraints on the unobscured star formation rates (SFRs) of DLAs to 2σ limits of $\dot{ψ }<0.09\hbox{-}0.27$ M⊙ yr −1, corresponding to SFR surface densities Σsfr < 10 −2.6 –10 −1.5 M⊙ yr −1 kpc −2 . The implications of these limits for the star formation law, metal enrichment, and cooling rates of DLAs are examined. By studying the distribution of impact parameters as a function of SFRs for all the galaxies detected around these DLAs, we place new direct constraints on the bright end of the UV luminosity function of DLA hosts. We find that ≤13 per cent of the hosts have $\dot{ψ }\ge 2$ M⊙ yr −1 at impact parameters $b_{\rm dla} \le (\dot{ψ }/{\rm M_{\odot }\, yr^{-1}})^{0.8}+6 \, \rm kpc$, differently from current samples of confirmed DLA galaxies. Our observations also disfavour a scenario in which the majority of DLAs arise from bright Lyman-break galaxies at distances 20 ≤ b dla < 100 kpc. These new findings corroborate a picture in which DLAs do not originate from highly star-forming systems that are coincident with the absorbers, and instead suggest that DLAs are associated with faint, possibly isolated, star-forming galaxies. Potential shortcomings of this scenario and future strategies for further investigation are discussed.